Bio-Conservation Learning Model Development With Waste Management Topic to Empower Environmental Awareness Character of Primary School Students - Ariati, Theodora Prahereni Novi; Saptono, Sigit; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2021)
This research was conducted because of the needs to empower the studensts’ environmental awareness character. This research aims to develop a bio-conservation learning model with waste management topics adapted from Project Based Learning model (PjBL) and inquiry and determine the influences of the bio-conservation learning model toward learning outcomes and students environmental awareness. This research is an ADDIE Research and Development. The model consists of Analysis, Design, Development, Implementation, and Evaluation. The subjects consisted of 93 third graders of 02 Santo Antonius Primary School.. The techniques of collecting data were interview, observation, questionnaire, and documentation. The product was a module for teachers with several contents, such as the bio-conservation model's characteristics, goals, and syntaxes. The validation result obtained a percentage of 88.6%. The N-gain of the first experimental group was 0.072 with high criteria. On the other hand, the second experimental group obtained a percentage of 0.514 with moderate criteria. The understanding of environmental awareness attitude was obtained by using a questionnaire and observational sheets. The obtained criteria were categorized high, with average scores of questionnaire 87.2% and observation 85.9%. This research showed the influence of learning outcomes and environmental awareness attitude after using the bio conservation model. The model implementation's emerging characters were waste management and 3R activities (Recycle, Reuse, and Reduce).